(untitled) (Diversity Research: Journal of Analysis and Trends, 2026)
The purpose of the article is to study the specific characteristics of machinery, equipment and vehicles and their application to valuation activities, to study the importance of the formation and effective development of the market for these property objects and the market for their valuation services. The author also substantiates the need to develop a generally accepted methodology for assessing the value of machinery and equipment as a criterion for determining the market value of machinery and equipment